'We don't need no education'? Exploring the educational experiences of young footballers. Issue 7 (3rd October 2018) - Platts, Chris; Smith, Andy
Abstract: Drawing upon data generated by 303 young male footballers employed in 21 professional clubs in England and Wales, this article explores some key aspects of players' masculinities, identities and engagement with education. Although many players described their educational experiences in largely negative terms, some aspired towards averageness, or middling, which is often central to working-class identifications with education. Other players found education 'easy', engaged in effortless achievement and had begun to internalize elements of the neoliberal achievement ideology. The propensity for players to engage in copying and pasting from the work of others, and to regard their courses as being almost impossible to fail, was consistent with neoliberal ideologies of credentialism and performativity. The findings suggest that a more nuanced understanding of young footballers' education is warranted, and their aspirations and experiences can at least be partly understood as responses to the prevailing neoliberal learning environments which they inhabit.